Hubungan Persepsi Orang Tua dengan Kelengkapan Imunisasi Dasar pada Bayi Usia 9-12 Bulan - Selvia, Mega; Rohmatin, Homsiatur; Supriyadi, Bagus (Universitas Nurul Jadid, 2024)
mmunization is a crucial preventive measure to protect children from infectious diseases. However, in Botolinggo, there are still parents who do not complete the basic immunization for their infants. This study aims to analyze the relationship between parental perception and the completeness of basic immunization in infants aged 9-12 months. A cross-sectional study design was employed, involving parents of infants aged 9-12 months in the working area of Botolinggo Health Center, Bondowoso Regency. The sample size of 63 respondents was determined using Power Analysis and selected through total sampling. Data were collected using a questionnaire and a basic immunization completeness assessment form, and subsequently analyzed using chi-square statistical analysis with a significance level of p < 0.05. The statistical test results showed X2 = 16.361 and p < 0.001, indicating a significant relationship between parental perception and the completeness of basic immunization. Parents with a positive perception are more likely to complete their infants' basic immunization. In conclusion, parental perception significantly influences behavior in completing infant immunization.